2019
DOI: 10.1111/imcb.12238
|View full text |Cite
|
Sign up to set email alerts
|

Modulating antibody‐dependent cellular cytotoxicity of epidermal growth factor receptor‐specific heavy‐chain antibodies through hinge engineering

Abstract: Human IgG1 and IgG3 antibodies (Abs) can mediate Ab‐dependent cellular cytotoxicity (ADCC), and engineering of the Ab Fc (point mutation; defucosylation) has been shown to affect ADCC by modulating affinity for FcRγIIIa. In the absence of a CH1 domain, many camelid heavy‐chain Abs (HCAbs) naturally bear very long and flexible hinge regions connecting their VHH and CH2 domains. To better understand the influence of hinge length and structure on HCAb ADCC, we produced a series of hinge‐engineered epidermal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We have previously observed similar induction of NK-degranulation by VRC01 IgG1 and IgG3 [14]. In contrast, a recent study found that hinge extension improved ADCC for one monoclonal antibody, but that this effect was not generalizable across specificities that recognized different epitopes on the same antigen [83]. Recognizing that there are numerous means to assess ADCC, we tested VRC01 hinge variant activity using HIV-1 Infectious Molecular Clone-infected target cells and assessing the reduction in luciferase expression as readout for cellular cytotoxicity [84].…”
Section: Impact Of Hinge Composition On Other Antibody Functionsmentioning
confidence: 68%
“…We have previously observed similar induction of NK-degranulation by VRC01 IgG1 and IgG3 [14]. In contrast, a recent study found that hinge extension improved ADCC for one monoclonal antibody, but that this effect was not generalizable across specificities that recognized different epitopes on the same antigen [83]. Recognizing that there are numerous means to assess ADCC, we tested VRC01 hinge variant activity using HIV-1 Infectious Molecular Clone-infected target cells and assessing the reduction in luciferase expression as readout for cellular cytotoxicity [84].…”
Section: Impact Of Hinge Composition On Other Antibody Functionsmentioning
confidence: 68%
“…Several studies have found that the length and flexibility of an antibody influences FcγR binding and ADCC activity (62)(63)(64)(65). However, there is no general consensus whether a short or a long hinge is beneficial for ADCC activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, S239D and I332E mutations improved FcγRIII binding and ADCC activity of a CD37 antibody (Heider et al, 2011; Lazar et al, 2006). Replacing the IgG1 hinge region with the longer hinge region from IgG3 or from a camelid antibody increased ADCC of an epidermal growth factor receptor antibody (D’Eall et al, 2019), while an IgG1 with E345R, E430G, and S440Y mutations formed hexamers that had greatly enhanced C1q binding and complement activation (Diebolder et al, 2014). The mutations T437R and K248E also promoted multimerization and improved effector functions of an OX40 receptor antibody (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%